THE ROLE OF RELATIONSHIP MARKETING IN BUILDING CUSTOMERS’ LOYALTY- A CASE STUDY OF THE MOBILE TELECOMMUNICATION INDUSTRY IN SOUTHERN PUNJAB-PAKISTAN - Ghafoor Awan, Abdul; Iqbal, Javed (British Journal of Marketing Studies, 2014)
The objective of this research paper is to assess the role of relationship marketing in winning customers’ loyalty in the mobile Phone industry in Pakistan. De-regularization of the telecommunication sector in Pakistan has created huge competition to capture the maximum market share. For this purpose, industry marketers and planners are exercising various relationship marketing strategies to attract new customers and retain the old ones. To analyze the role of relationship marketing in building customers’ loyalty, the author has selected four independent variables such as service quality, price perception, brand image and value offers while customer’s loyalty is taken as dependent variable. A structured questionnaire containing 24 closed ended questions was developed to collect data from the field. The data was analyzed through Likert- scale. This scale is defined with 5 options of strongly agree on 5 and strongly disagree on 1. In order to check the reliability of the variables, a reliability test was conducted on 20 respondents of different age groups with different occupations. The results of this test showed positive significant relationship among the variables. The results of this study are robust and consistent with previous studies. This study provides in-depth knowledge about mobile users and cellular companies operating in Pakistan can take benefit from it.The finding of this research study is expected to be beneficial for the managers of the mobile operators in their decisions relating to the relationship marketing issues that are connected with the needs of the customers. These needs and interests of the customers, in turn, can increase their revenue and profits in the long-run.